Social Cost Benefit Analysis of Solar Power Projects - Natarajan, P.; Nalini, G. S. (Prabandhan: Indian Journal of Management, 2015)
Social cost benefit analysis provides a scientific base for the appraisal of projects with a view to determine whether the total social benefits of a project justify the total social costs. India is endowed with immense solar energy potential as it is located in the tropical zone of the earth. The Government of India launched The Jawaharlal Nehru National Solar Mission with the intention to be a global leader in solar energy. Since solar power is in the nascent stage in our country, it is mandatory to assess its impact on the society. Solar power guarantees various benefits, including carbon credit, renewable energy certificate, employment generation, rural electrification, curbing global warming, and also ensures overall development. However, the main setback of solar power is its high generation cost. This study unveiled that the social benefits attained in case of solar power are greater than the social cost. However, the high startup capital keeps the customers away from solar power. Thus, necessary measures need to be taken to bring down the cost of solar power to ensure its viability. Also, the government has to initiate the right mechanisms to discard the electronic scraps.